Automatic Identification of Maritime Boundary Alert System using GPS - Kavitha, A; Ashok Kumar, N; Revathy, M (International Journal of Engineering and Technology, 2018)
Global Positioning System (GPS) is being used more and more for a wide range of applications. This is a reliable position, navigation for end-users of anywhere in the world or around the globe, on any weather, day or night. The synchronization benefit gives that the GPS has three segments: space, control and client GPS has turned into a broadly utilized route apparatus over the world and turn into a helpful instrument for mapping, overviews, business, logical utilizations, checking and diversion has gone. As in any of the current GPS systems of geographic and entertainment, the security requirements of civilian navigation in the sea are met because the sea border of a country cannot be marked. This work concentrates on the flexibility and utility of a GPS in the ocean. The principle motivation behind the work is to help anglers explore past the limits of different nations. In the event that an angler goes past the limits of the nation, at that point a notice emerges, showing that the anglers have crossed the outskirt. Furthermore, a GSM transmitter interface will make an impression on construct station situated with respect to the shore showing that a vessel has crossed the fringe. Hence protects in the shore can help and give extra help to those anglers if necessary. Remembering about existences of Indian anglers, this gadget has been made to help them not to move past Indian. Overall, it is an endeavor to fabricate an appropriate gadget for the anglers at a sensibly ease.Â Â